Evolution and prediction of the extreme rainstorm event in July 2021 in Henan province, China - Dong Chen; Chaoying Pan; Shaobo Qiao; Rong Zhi; Shankai Tang; Jie Yang; Guolin Feng; Wenjie Dong (Atmospheric Science Letters, 2023)
Abstract The Once‐in‐a‐Century extreme rainstorm event caused severe floods over Henan province during July 18–21, 2021, which resulted in large casualty and property losses. Although the rainstorm event occurred in Henan after July 18, the excessive rainfall had occurred to the east of Henan before July 18, with the 4‐day accumulated rainfall exceeding +130 mm during July 14–17, 2021. How the rainfall evolving westward and intensifying after July 18 remained a puzzle, which is the focus of this study. The prerainstorm stage (July 14–17) was related to the South Asian High (SAH) extending eastward and the western Pacific subtropical high (WPSH) extending northwestward, and a low vortex between the SAH and WPSH caused above‐normal rainfall to the east of Henan. The rainstorm stage (July 18–21) was associated with an inverted trough and excessive southerly and southeasterly water vapor transportation above Henan, which resulted from the combined effects of a deep trough in the upper troposphere and typhoon activities. Additionally, three subseasonal forecasting systems predicted this rainstorm event 3 days in advance, with the European Center for Medium Range Weather Forecasts (ECMWF) performing the best, which was related to a better prediction of the inverted trough and the water vapor transportation in the middle‐lower troposphere. These results advance our understanding of the extreme rainstorm event in July 2021 in Henan.